Bacterial Cellulose: Natural Biomaterial for Medical and Environmental Applications - Pooja Deshpande; Shashwati Wankar; Sakshi Mahajan; Yogesh Patil; Jyutika Rajwade; Atul Kulkarni (Journal of Natural Fibers, 2023)
Extensive research has been conducted during 20th century to discover renewable natural polymers that are sustainable. Cellulose represents one such biomaterial which is abundant, renewable, and biodegradable. Both plant and microbial biomass can be processed to make cellulose. Bacterial cellulose (BC) is a prospective natural polymer produced by certain bacteria during their growth phase. BC is hydrophilic biopolymer, fibrous (20–100 nm diameter), and biocompatible. In contrast to plant cellulose, BC has the benefit of being in form, which is both, highly crystalline and extremely pure. This review provides a crisp summary of the synthesis and functionalization of BC, and its applications in the fields of biomedicine and the environment.